Pharmacokinetics, Pharmacodynamics and Allometric Scaling of Chloroquine in a Murine Malaria Model - Moore, Brioni; Page-Sharp, Madhu; Stoney, Jillian; Ilett, K.; Jago, Jeffrey; Batty, Kevin (American Society for Microbiology, 2011)
Chloroquine (CQ) is an important antimalarial drug for the treatment of special patient groups and as a comparator for preclinical testing of new drugs. Pharmacokinetic data for CQ in animal models are limited; thus, we conducted a three-part investigation, comprising (i) pharmacodynamic studies of CQ and CQ plus dihydroartemisinin (DHA) in Plasmodium berghei-infected mice, (ii) pharmacokinetic studies of CQ in healthy and malaria-infected mice, and (iii) interspecies allometric scaling for CQ from 6 animal and 12 human studies. The single-dose pharmacodynamic study (10 to 50 mg CQ/kg of body weight) showed dose-related reduction in parasitemia (5- to >500-fold) and a nadir 2 days after the dose. Multiple-dose regimens (total dose, 50 mg/kg CQ) demonstrated a lower nadir and longer survival time than did the same single dose. The CQ-DHA combination provided an additive effect compared to each drug alone. The elimination half-life (t1/2), clearance (CL), and volume of distribution (V) of CQ were 46.6 h, 9.9 liters/h/kg, and 667 liters/kg, respectively, in healthy mice and 99.3 h, 7.9 liters/h/kg, and 1,122 liters/kg, respectively, in malaria-infected mice. The allometric equations for CQ in healthy mammals (CL = 3.86 × W0.56, V = 230 × W0.94, and t1/2 = 123 × W0.2) were similar to those for malaria-infected groups. CQ showed a delayed dose-response relationship in the murine malaria model and additive efficacy when combined with DHA. The biphasic pharmacokinetic profiles of CQ are similar across mammalian species, and scaling of specific parameters is plausible for preclinical investigations.